2008
DOI: 10.1136/jech.2008.077354
|View full text |Cite
|
Sign up to set email alerts
|

Welfare state regimes, unemployment and health: a comparative study of the relationship between unemployment and self-reported health in 23 European countries

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
326
3
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(371 citation statements)
references
References 46 publications
12
326
3
21
Order By: Relevance
“…status deprivation, loss of time structure) (Bartley 1994;Mathers and Schofield 1998;Creed and Macintyre 2001). Additionally, a changing association between unemployment and health during economic change and systematic differences in the effects of employment status on health between countries has been recently described (Béland et al 2002;Ahs and Westerling 2006;Arber and Lahelma 1993;Bambra and Eikemo 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…status deprivation, loss of time structure) (Bartley 1994;Mathers and Schofield 1998;Creed and Macintyre 2001). Additionally, a changing association between unemployment and health during economic change and systematic differences in the effects of employment status on health between countries has been recently described (Béland et al 2002;Ahs and Westerling 2006;Arber and Lahelma 1993;Bambra and Eikemo 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Increasing research has recently focused on examining systematic differences in the magnitude of inequalities between regions, countries or groups of countries (Mackenbach et al 2008;Bambra and Eikemo 2009;Eikemo et al 2008b) and trends in health inequalities within countries Avendano et al 2005;Mackenbach et al 2003;Lahelma et al 2002;Dalstra et al 2002;Mazzuco and Suhrcke 2010 online first). As of currently, research has shown that health inequalities in Europe have increased in some but not all countries and that there is considerable variation in the corresponding trends by gender, health or socio-economic indicator and measure of inequality.…”
Section: Introductionmentioning
confidence: 99%
“…As Bambra and Eikemo (2009) recently showed, the associations between employment status and health play out differently in different countries. Several studies have found positive health effects of combining employment and family for women, including lone mothers *Manuscript without Author Details Click here to view linked References 2 (Fokkema 2002;Lahelma, Arber et al 2002;Artazcoz, Borrell et al 2004;Zabkiewicz 2010).…”
Section: Introductionmentioning
confidence: 99%
“…En effet, il a été montré que l'environnement social et institutionnel influence de manière significative la relation entre chômage et mortalité [36,37]. Par exemple, cette relation est beaucoup moins forte dans un pays comme l'Allemagne, où le filet de protection sociale est substantiellement déve-loppé, que dans un pays comme les États-Unis où il est maintenu à un minimum [38].…”
Section: Les Difficultés Pour Transposer Les éTudes Réalisées Dans D'unclassified
“…Par exemple, cette relation est beaucoup moins forte dans un pays comme l'Allemagne, où le filet de protection sociale est substantiellement déve-loppé, que dans un pays comme les États-Unis où il est maintenu à un minimum [38]. En France, où les individus vivent avec un filet social relativement protecteur par rapport à beaucoup d'autres pays, à la fois concernant l'indemnisation du chômage (montant et délai de mise en place des indemnités, période pendant laquelle elles sont versées) [36] et la couverture des soins médicaux [39], on peut prédire que les effets délétères du chômage, tels que la réduction de revenu ou FAITS ET CHIFFRES REPÈRES cohorte à la population française en tenant compte du taux de chô-mage actuel et des chiffres de mortalité dans la tranche d'âge considérée, donne un chiffre de 14 000 décès imputables chaque année au chômage. Il ne s'agit évidemment que d'une estimation, à cause de la non-représentativité de la cohorte et de certaines limitations liées à des données incomplètes (sur la durée du chômage, notamment), mais elle fournit un ordre de grandeur suggérant que les quelques centaines de suicides annuels liés au chômage en France [41] ne seraient que la partie émergée de l'iceberg et que le problème de santé publique serait beaucoup plus vaste.…”
Section: Les Difficultés Pour Transposer Les éTudes Réalisées Dans D'unclassified